Circulating MAIT cells in multiple sclerosis and amyotrophic lateral sclerosis - De Federicis, Davide; Bassani, Claudia; Chiarelli, Rosaria Rita; Montini, Federico; Giordano, Antonino; Esposito, Federica; Riva, Nilo; Quattrini, Angelo; Martinelli, Vittorio; Filippi, Massimo; Farina, Cinthia (Frontiers in Immunology, 2024)
Neurological disorders, including multiple sclerosis (MS) and amyotrophic lateral sclerosis (ALS), may be associated with alterations in blood cell composition and phenotype. Here, we focused our attention on circulating mucosal-associated invariant T (MAIT) cells, a CD8+ T cell memory population expressing the invariant Vα7.2 region in the T cell receptor and high surface levels of the CD161 marker. Transcriptomics data relative to peripheral blood mononuclear cells (PBMC) highlighted downregulation of CD161 and other MAIT-associated markers in progressive MS and not relapsing remitting (RR)-MS when gene expressions relative to each disease course were compared to those from healthy controls. Multiparametric flow cytometry of freshly isolated PBMC samples from untreated RR-MS, primary or secondary progressive MS (PP- or SP-MS), ALS and age- and sex-matched healthy controls revealed specific loss of circulating CD8+ MAIT cells in PP-MS and not other MS courses or another neurological disorder such as ALS. Overall, these observations point to the existence of immunological changes in blood specific for the primary progressive course of MS that may support clinical definition of disease.